Effect of Powder Particle Size on Solvent Free Membrane for 3D Hybrid Scaffold Structure - Suntornnond, R. (2016)
Solvent free membrane fabrication is a powder based method that can generate porous structure without used of organic solvent that can harmful to cell both in vitro and in vivo. In this paper, the effect of powder size on membrane morphology and surface wettability were investigated. Two different Poly (ε-caprolactone), (PCL) particle sizes of powder which are 100 µm and 500 µm were used. Powder was spread on top of water and by heating with laboratory oven in was melted down. After 10-15 minutes, it was fully melted and membrane can be obtained after cooled down. The powder was really affect morphology of membrane both macroscopic level and microscopic level. For macroscopic level, 500 µm membrane for different surface texture between water contact side and air contact side which air contact side gave smoother surface. On the other hand, for microscopic level, 100 µm showed more porous structure. Lastly, by further investigate the surface properties using contact angle, it confirmed that there is no significant between two different sides of 100 mm membrane but for 500 mm membrane it showed different manner because the contact angle results that was around 10 degree different between two sides.